Chasing the rate: An interrupted time series analysis of interventions targeting reported hospital onset Clostridioides difficile, 2013–2018. (4th October 2020) - Doll, Michelle E.; Zhao, Jinlei; Kang, Le; Rittmann, Barry; Alvarez, Michael; Fleming, Michele; Cooper, Kaila; Stevens, Michael P.; Bearman, Gonzalo
Abstract: Objective: To assess the impact of major interventions targeting infection control and diagnostic stewardship in efforts to decrease Clostridioides difficile hospital onset rates over a 6-year period. Design: Interrupted time series. Setting: The study was conducted in an 865-bed academic medical center. Methods: Monthly hospital-onset C. difficile infection (HO-CDI) rates from January 2013 through January 2019 were analyzed around 5 major interventions: (1) a 2-step cleaning process in which an initial quaternary ammonium product was followed with 10% bleach for daily and terminal cleaning of rooms of patients who have tested positive for C. difficile (February 2014), (2) UV-C device for all terminal cleaning of rooms of C. difficile patients (August 2015), (3) "contact plus" isolation precautions (June 2016), (4) sporicidal peroxyacetic acid and hydrogen peroxide cleaning in all patient areas (June 2017), (5) electronic medical record (EMR) decision support tool to facilitate appropriate C. difficile test ordering (March 2018). Results: Environmental cleaning interventions and enhanced "contact plus" isolation did not impact HO-CDI rates. Diagnostic stewardship via EMR decision support decreased the HO-CDI rate by 6.7 per 10, 000 patient days ( P = .0079). When adjusting rates for test volume, the EMR decision support significance was reduced to a difference of 5.1 case reductions per 10, 000 patient days ( P = .0470). Conclusion: Multiple aggressively implemented infection control interventions targeting CDI demonstrated a disappointing impact on endemic CDI rates over 6 years. This study adds to existing data that outside of an outbreak situation, traditional infection control guidance for CDI prevention has little impact on endemic rates.